Preparation of Electrochemical Sensor for Paracetamol Detection Based on a New Piperazine Substituted Triazole-Coumarin Hybrid Doped PEDOT Modified Flexible HOPG Electrode - Arvas, Busra; Yazar, Sibel; Arvas, Melih Besir; Eglence-Bakir, Songuel; Sahin, Musa; Yolacan, Cigdem (ELECTROCHEMICAL SOC INC, 2023)
This study includes the electrochemical determination of paracetamol (PC), using novel piperazine substituted triazole-coumarin hybrids doped PEDOT coated highly oriented pyrolytic graphite (HOPG) electrode. For the electrochemical determination of paracetamol, using an electrode prepared by a one step electropolymerization of the new triazole-tethered piperazine coumarin hybrid doped PEDOT conductive polymer on the HOPG substrate was mentioned. The electrodes were characterized by FT-IR, SEM and XRD analysis. The possible interference effects of Ascorbic acid, Uric acid, Dopamine, Glucose and Caffeine were investigated by chronoamperometry in the presence of paracetamol. The sensor (PEDOT-MC1/HOPG-10 Scan) has a high sensitivity to paracetamol, with a limit of detection (LOD) of 0.312 mu m and a RSD % of 1.22 (S/N = 3). In addition, real sample analyzes were performed on pharmaceutical samples for PC determination using the prepared sensor (PEDOT-MC1/HOPG-10 Scan). The novelty of this paper is the use of new piperazine substituted triazole-coumarin hybrid doped PEDOT material for the first time in the literature, as well as a new electrode substrate material for the determination of paracetamol and the use of HOPG (Highly oriented pyrolytic graphite), which exhibits higher electroanalytical performance than other carbon-based materials. (c) 2023 The Electrochemical Society (ECS). Published on behalf of ECS by IOP Publishing Limited.
Keywords: ACETAMINOPHEN; PHARMACEUTICALS; CONDUCTIVITY; ENHANCEMENT; DERIVATIVES; PHOSPHATE; BEHAVIOR; FACILE; FILM; Materials Science; Physics